Exploring the psychological mechanism linking nightmares to increased self-harm risk - Hochard, Kevin D. (2014)
Nightmares, a common sleep disturbance which provoke fearful awakening, have been found to be a significant predictor of suicidal thoughts and behaviours. The research presented in this thesis aims to firstly examine if nightmares are predictive of self-harm regardless of suicidal intent or motivation, and secondly to explore the psychological mechanism linking the occurrence of nightmares to self-harm. Chapter 2, an online survey, revealed that nightmares were a significant predictor of self-harm regardless of suicidal intent or motivation and that this relationship remained when controlling for the effects of depressive symptoms. High levels of nightmares were also associated with elevated levels of negative affect and defeat. Chapter 3 prospectively examined the direction of the predictive relationship between nightmares and self-injurious thoughts and behaviours (SITBs) through a 5-day diary study of undergraduate students. Nightmares unidirectionally predicted SITBs when controlling for depressive symptoms and negative affect. Mediation analysis revealed negative affect to be a partial mediator between nightmares and post-sleep SITBs. Chapter 4 explored differences in the linguistic content of nightmares in individuals with and without a history of self-harm, using nightmare reports prospectively obtained from participants taking part in the diary study. Contrary to the literature, participants with a history of self-harm did not report more words pertaining to death. Exploratory analysis investigating self-harm recency indicated a higher frequency of perceptual words such as ‘feel’ and body words such as ‘arm’ in participant with current self-harm (< 1 month) compared to those with a history of self-harm (> 1 month) and those without. Chapter 5 modelled the psychological mechanism linking nightmares to increased self-harm risk via structural equation modeling from survey data. This model incorporated negative affect, hyperarousal and a latent variable ‘self-harm cues’ building on our previous findings and the literature. Our retained model indicated that a 1 standard deviation increase in nightmare score increased the probability of participants having recently (< 1 month) engaged in self-harm. Chapter 6 tested the predictions of the model computed in the previous chapter using behavioural and psycho-physiological methodology. Psycho-physiological measures when exposed to negatively valenced stimuli did not reveal any differences between high and low nightmare participants, nor were differences observed in self-harm cue sensitivity. However, a medium effect was observed indicating the high nightmare group to be more sensitive to stressors. These findings are discussed in the context of the literature in Chapter 7. They provide novel insights into the relationship between nightmares and self-harm, and highlight the importance of negative affect and hyperarousal as reducing stress resilience in individuals at risk of deliberate self-injury.